Historical evaluation of the in vivo adventitious virus test and its potential for replacement with next generation sequencing (NGS). (February 2023) - Barone, Paul W.; Keumurian, Flora J.; Neufeld, Caleb; Koenigsberg, Andrea; Kiss, Robert; Leung, James; Wiebe, Michael; Ait-Belkacem, Rima; Azimpour Tabrizi, Chakameh; Barbirato, Cristina; Beurdeley, Pascale; Brussel, Audrey; et al.
Abstract: The Consortium on Adventitious Agent Contamination in Biomanufacturing (CAACB) collected historical data from 20 biopharmaceutical industry members on their experience with the in vivo adventitious virus test, the in vitro virus test, and the use of next generation sequencing (NGS) for viral safety. Over the past 20 years, only three positive in vivo adventitious virus test results were reported, and all were also detected in another concurrent assay. In more than three cases, data collected as a part of this study also found that the in vivo adventitious virus test had given a negative result for a sample that was later found to contain virus. Additionally, the in vivo adventitious virus test had experienced at least 21 false positives and had to be repeated an additional 21 times all while using more than 84, 000 animals. These data support the consideration and need for alternative broad spectrum viral detection tests that are faster, more sensitive, more accurate, more specific, and more humane. NGS is one technology that may meet this need. Eighty one percent of survey respondents are either already actively using or exploring the use of NGS for viral safety. The risks and challenges of replacing in vivo adventitious virus testing with NGS are discussed. It is proposed to update the overall virus safety program for new biopharmaceutical products by replacing in vivo adventitious virus testing approaches with modern methodologies, such as NGS, that maintain or even improve the final safety of the product.